2002
DOI: 10.1034/j.1600-0765.2002.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of combined effects of cyclosporin and nifedipine on gingival overgrowth in rats

Abstract: It has previously been shown that, while cyclosporin A (CsA) and nifedipine both cause gingival overgrowth in the rat, the combined use of these drugs increases the severity of overgrowth. The aim of this study was to describe the histometry and densities of fibroblasts, collagen fibers and vessels in the gingival tissue of rats that were treated with CsA and nifedipine, either alone or in combination. Rats were treated for 60 days with a daily subcutaneous injection of 10 mg/kg body weight of CsA and/or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
23
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
9
23
1
Order By: Relevance
“…Our histomorphometric and stereological results showed that no signs of gingival overgrowth were found in the group administered sirolimus alone, whereas prominent gingival overgrowth was found in groups administered cyclosporine A alone and tacrolimus alone. Many clinical and experimental studies reported that combined drug usage caused much more gingival overgrowth compared with the usage of each drug alone . In contrast to these studies, the results of the present study showed that gingival overgrowth was more prominent in groups administered cyclosporine A and tacrolimus alone compared with combination groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Our histomorphometric and stereological results showed that no signs of gingival overgrowth were found in the group administered sirolimus alone, whereas prominent gingival overgrowth was found in groups administered cyclosporine A alone and tacrolimus alone. Many clinical and experimental studies reported that combined drug usage caused much more gingival overgrowth compared with the usage of each drug alone . In contrast to these studies, the results of the present study showed that gingival overgrowth was more prominent in groups administered cyclosporine A and tacrolimus alone compared with combination groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with the macroscopic examination, the histometric findings showed that epithelial thickness and connective tissue width were increased in groups 5, 6, and 7 and connective tissue height was increased in groups 5 and 7, where remarkable gingival overgrowth was observed. These results are consistent with previous findings that showed increased thickness of epithelium and connective tissue 6,22 . Those authors also reported increases in the density of fibroblasts and collagen fibers.…”
Section: Discussionsupporting
confidence: 93%
“…Immunosuppressive agents and calcium channel blockers are used together to treat post‐transplant high blood pressure and decrease nephrotoxicity 20 . In many clinical studies, combined use of nifedipine and tacrolimus in transplant patients was reported to cause more severe gingival overgrowth than nifedipine or tacrolimus alone 5,8,10,11,21‐24 …”
mentioning
confidence: 99%
“…This observation is in accordance with the earlier studies. [10141522] In one of the recent experimental studies using the rat model, authors reported DIGO only after 24 weeks of administration of tacrolimus and Nf, alone or in combination. [23] Differences of drug doses were accounted as the possible reason for such variation in findings.…”
Section: Discussionmentioning
confidence: 99%